2021
DOI: 10.26508/lsa.202101183
|View full text |Cite
|
Sign up to set email alerts
|

β-arrestin1 promotes tauopathy by transducing GPCR signaling, disrupting microtubules and autophagy

Abstract: G protein–coupled receptors (GPCRs) have been shown to play integral roles in Alzheimer’s disease pathogenesis. However, it is unclear how diverse GPCRs similarly affect Aβ and tau pathogenesis. GPCRs share a common mechanism of action via the β-arrestin scaffolding signaling complexes, which not only serve to desensitize GPCRs by internalization, but also mediate multiple downstream signaling events. As signaling via the GPCRs, β2-adrenergic receptor (β2AR), and metabotropic glutamate receptor 2 (mGluR2) prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…This data is in agreement with the inhibitory effect of β-arrestin1 on the formation of LC3 puncta and the reduction in p62-LC3 colocalization. These data are consistent with the observed role of β-arrestin1 in impeding p62/SQSTM1 flux and impairing destruction of misfolded tau ( 83 ) and underline the potential of β-arrestin proteins as drug targets for the therapy of neurodegenerative diseases. FTD includes a spectrum of clinical syndromes associated with various neurodegenerative diseases.…”
Section: The Role Of β-Arrestin Proteins In Cytoskeleton-associated N...supporting
confidence: 88%
See 1 more Smart Citation
“…This data is in agreement with the inhibitory effect of β-arrestin1 on the formation of LC3 puncta and the reduction in p62-LC3 colocalization. These data are consistent with the observed role of β-arrestin1 in impeding p62/SQSTM1 flux and impairing destruction of misfolded tau ( 83 ) and underline the potential of β-arrestin proteins as drug targets for the therapy of neurodegenerative diseases. FTD includes a spectrum of clinical syndromes associated with various neurodegenerative diseases.…”
Section: The Role Of β-Arrestin Proteins In Cytoskeleton-associated N...supporting
confidence: 88%
“…β-arrestin2 protein and mRNA were significantly increased in the tau-FTD brain samples compared to the controls and in the brain samples of the P301S transgenic mice compared to the brains of the non-transgenic mice ( 85 ). A recent report has shown that β-arrestin1 levels are increased in the brains of FTD patients, and β-arrestins are essential for the β2 adrenergic receptor and mGluR2 glutamate receptor-mediated increase in pathogenic tau ( 83 ). Increased β-arrestin1 also causes the accumulation of pathogenic tau, whereas its reduction alleviates tau-induced pathology and rescues the impaired synaptic plasticity and cognitive abilities in PS19 mice.…”
Section: The Role Of β-Arrestin Proteins In Cytoskeleton-associated N...mentioning
confidence: 99%
“…S3C ). To measure functional changes in synaptic plasticity imposed by the CHCHD2-T61I mutation, we carried out electrophysiological studies from ex vivo brain slices as we previously showed ( 35 ). Long-term potentiation (LTP) induced by theta-burst stimulation showed that 10-month-old CHCHD2-T61I Tg line U144 mice exhibit a significant reduction in hippocampal LTP compared with WT littermates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We performed four different experimental assays [ 11 ] to determine the extent of β-arrestin binding. A proximity ligation assay [ 11 , 33 , 34 ] in transfected HEK-293 cells ( Figure 4 ) showed that C5-S and C6-S evoked β-arrestin binding to β 2 AR to approximately the same extent as the partial, balanced, β-agonist albuterol (ALB). In contrast, C-1S exhibited no β 2 AR: β-arrestin binding.…”
Section: Ascertainment Of Gs-biasing With Selected Compoundsmentioning
confidence: 99%